Method for suppressing formation of biofilm in drain pipe, method for suppressing formation of biofilm, method for suppressing formation of scale, and method for suppressing formation of biofilm and scale

JP2025031705APending Publication Date: 2025-03-07TAIKOH CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
JP2024145027
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2023-08-25
Filing Date
2024-08-26
Publication Date
2025-03-07

AI Technical Summary

Benefits of technology

【0016】 以上、本発明によって、バイオフィルムの抑制によるスケール形成抑制方法を提供することができる。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025031705000001_ABST
    Figure 2025031705000001_ABST
Patent Text Reader

Abstract

To provide a method for suppressing formation of a scale by suppressing a biofilm.SOLUTION: A method for suppressing formation of a biofilm according to one aspect of the present invention comprises a step of applying paint containing an antibacterial agent to a drainage pipe in a facility made of resin or metal. Also, a method for suppressing formation of a scale in a drainage pipe according to another aspect of the present invention comprises a step of applying paint containing an antibacterial agent to a drainage pipe in a facility. Further, a method for suppressing formation of a scale and a biofilm in a drainage pipe according to another aspect of the present invention comprises a step of applying paint containing an antibacterial agent to a drainage pipe in a facility.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a method for inhibiting biofilm formation in a drainage pipe, a method for inhibiting biofilm formation, a method for inhibiting scale formation, and a method for inhibiting these formations. [Background technology]

[0002] Scale that forms on the inner walls of pipes is found to a greater or lesser extent in all systems, from water pipes to sewer pipes. The presence of scale can cause foul odors in buildings and cause drainage to stop flowing, resulting in blockages. Furthermore, because scale comes into contact with the interior of the pipe in a solidified state, it can come into contact with the interior wall of the pipe as it peels off, and even damage the wall. This risk is particularly high when the pipe is made of resin. For example, Patent Document 1 below describes a technology for removing scale that has formed inside pipes. [Prior art documents] [Patent documents]

[0003] [Patent Document 1] JP 2002-239488 A Summary of the Invention [Problem to be solved by the invention]

[0004] However, the above-mentioned techniques are intended to rehabilitate the pipes by removing the scale that has formed, and are not intended to suppress the formation of scale itself.

[0005] On the other hand, the main cause of scale is biofilms formed by interactions between bacteria and the inner walls of materials, and it is believed that suppressing the formation of biofilms can ultimately suppress the formation of scale.

[0006] In addition, the sewer pipes of apartment buildings need to be properly descaled so that residents can live comfortably in a safe and sanitary environment. In extreme cases, the building may emit a foul odor, the drainage may not flow, and clogging may occur. In order to reduce scale, it is important to properly suppress the biofilm that is the source of the scale.

[0007] In view of the above problems, an object of the present invention is to provide a method for inhibiting scale formation by inhibiting biofilms. [Means for solving the problem]

[0008] A method for inhibiting scale formation according to one aspect of the present invention that solves the above-mentioned problems includes applying paint containing an antibacterial agent to drainage pipes in a facility that are made of resin or metal.

[0009] Also, in this respect, although not limited thereto, it is preferable that the drain pipe is a polyvinyl chloride pipe.

[0010] Also, in this respect, although not limited thereto, it is preferable that the drain pipe be made of carbon steel.

[0011] In addition, in this respect, although not limited thereto, it is preferable that the drain pipe is a metal pipe having a zinc-plated inner surface.

[0012] In addition, in this respect, although not limited thereto, the antibacterial agent is preferably silver-loaded zeolite.

[0013] In addition, in this respect, although not limited thereto, the weight of the antibacterial agent is preferably within the range of 2 to 10 parts by weight, where the weight of the entire paint is taken as 100 parts by weight.

[0014] A method for inhibiting scale formation in a drainage pipe in another aspect of the present invention includes a step of applying paint containing an antibacterial agent to a drainage pipe in a facility.

[0015] In addition, a method for inhibiting the formation of scale and biofilm in a drainage pipe in another aspect of the present invention includes a step of applying paint containing an antibacterial agent to a drainage pipe in a facility. Effect of the Invention

[0016] As described above, the present invention can provide a method for inhibiting scale formation by inhibiting biofilms. [Brief description of the drawings]

[0017] [Figure 1] 1 is a diagram showing an outline of antibacterial protective piping according to an embodiment; [Diagram 2] 1 is a diagram showing an outline of an antibacterial protection method for producing antibacterial protection piping according to an embodiment of the present invention; [Diagram 3] 1 is a diagram showing an outline of an antibacterial protection method for producing antibacterial protection piping according to an embodiment of the present invention; [Figure 4] FIG. 1 is an image diagram of piping for conducting a biofilm evaluation test to examine the effects of the invention according to an embodiment. [Diagram 5] 11A to 11C are photographs showing the inside of each sample pipe one month after the start of an exposure test according to the embodiment. [Figure 6] 11A and 11B are photographs of the inside of each sample pipe seven months after the start of an exposure test according to the embodiment. [Figure 7] FIG. 13 is a diagram showing the absorbance inside each sample pipe one month after the start of an exposure test according to the embodiment. [Figure 8] FIG. 13 is a diagram showing the absorbance inside each sample pipe seven months after the start of an exposure test according to the embodiment. [Figure 9] FIG. 13 is a diagram showing the biofilm index inside each sample pipe one month after the start of an exposure test according to the embodiment. [Figure 10] FIG. 13 is a diagram showing the biofilm index inside each sample pipe seven months after the start of the exposure test according to the embodiment. BEST MODE FOR CARRYING OUT THEINVENTION

[0018] Hereinafter, the embodiments of the present invention will be described in detail with reference to the drawings. However, the present invention can be embodied in many different forms, and is not limited to the specific examples in the embodiments and examples shown below.

[0019] 1 is a schematic diagram showing a covered and protected pipe (hereinafter referred to as "this protected pipe") 1 to which a biofilm inhibition method according to the present embodiment and a scale formation inhibition method based thereon (hereinafter referred to as "this method") are applied. This protected pipe 1 can be produced by carrying out this method, which will be described in detail later.

[0020] As shown in this figure, the protective pipe 1 comprises a cylindrical pipe 2 made of resin or metal, and a resin layer 3 adhered to the inner surface of the cylindrical pipe 2, and the resin layer 3 contains an antibacterial agent containing silver zeolite with an average particle size of 0.1 μm to 100 μm in the range of 1 wt % to 5 wt %, and has a thickness in the range of 0.5 mm to 3 mm.

[0021] Moreover, this protective pipe 1 is obtained by cutting the inside of the cylindrical pipe 2, which has been used and has rust or the like on its inner surface, and coating it with a resin layer. That is, the inner surface of the cylindrical pipe, which has rust on its inner surface, is polished with an abrasive to be smooth, and its length is the same as the length of the installed pipe. Specifically, the length of this protective pipe 1 can be adjusted as appropriate, and is preferably in the range of 30 cm to 5 m, although it is not limited thereto.

[0022] The antibacterial protection method for inside a pipe for producing a coated and protected pipe according to this embodiment (hereinafter referred to as "this method") includes the steps of (1) removing rust inside the pipe by polishing, and (2) applying and curing an antibacterial paint containing 1% by weight or more and 5% by weight or less of a silver-containing antibacterial agent in a resin material. Figures 2 and 3 are diagrams showing an outline of the steps of this method.

[0023] First, the method includes the step of (1) removing rust from inside a pipe by polishing.

[0024] Here, the process of removing rust by polishing can use various methods, but is not limited to these. For example, a method can be used in which an abrasive having multiple blade members formed around an axis member is connected to a wire, and the inside of the pipe is sucked from the outlet side to create a low pressure state and rotated to physically scrape off rust and the like that has adhered to the inside of the pipe, but is not limited to these.

[0025] The method also includes (2) applying and curing an antibacterial paint containing 1% by weight or more and 5% by weight or less of an antibacterial agent containing silver in a resin material.

[0026] In this method, it is preferable that the resin material is in a low viscosity state when poured into the pipe, but is sufficiently solidified (cured) after a certain amount of time has passed since it is applied to the inside of the pipe. Specifically, one preferable example is an epoxy resin that is cured by mixing a base resin and a curing agent.

[0027] In this case, the ratio of the base agent and the curing agent is not limited as long as the resin material can be solidified, but it is preferable that the number of epoxy groups in the base agent and the number of active hydrogens in the curing agent are approximately the same. Specifically, it is preferable to mix the epoxy equivalent in the base agent and the active hydrogen equivalent in the curing agent to be 1:1, but it is also necessary to have a certain range, specifically, about 1:0.9 to 1.1. In addition, the weight ratio of the base agent and the curing agent is also not limited as long as it can be sufficiently cured as described above, but in general, when the weight of the base agent is 1, it is preferable that it is about 0.2, specifically, 0.15 to 0.25, but is not limited thereto.

[0028] In this method, the antibacterial agent contains silver. By containing silver, an antibacterial effect can be achieved. Although the silver is not limited, it is preferable that the silver is fine silver particles from the viewpoint of enhancing dispersion performance. The diameter of the silver fine particles is not limited as long as it can be dispersed sufficiently evenly, but for example, the average particle diameter is preferably 0.1 μm or more and 100 μm or less, and more preferably 10 μm or less. By making it 0.1 μm or more, it is possible to obtain the antibacterial effect of the silver fine particles, and by making it 100 μm or less, it is possible to stably disperse the silver fine particles in a thin film without reducing the adhesive performance of the film even when the silver fine particles are applied inside a pipe.

[0029] In the present method, the silver is preferably silver zeolite, which has the effect of achieving antibacterial and deodorizing properties.

[0030] In addition, in this method, as described above, it is preferable that the antibacterial agent is contained in an amount of 1% by weight or more and 5% by weight or less based on the total weight of the paint. By containing 1% by weight or more, the antibacterial effect can be exerted, and by containing 5% by weight or less, sufficient adhesive strength can be maintained. Specifically, antibacterial agents generally do not have adhesive properties, and by containing a large amount of the agent, while the antibacterial properties can be maintained, the adhesive properties as a film may decrease. In particular, since piping passes fluids such as water through the inside, there is a possibility that the piping may peel off due to these. Therefore, careful consideration is required to maintain sufficient adhesive properties and sufficient hardness as a layer.

[0031] In this method, the thickness of the antibacterial paint to be applied, preferably the thickness of the resin layer after solidification, is not limited, but is preferably in the range of 0.5 mm to 3 mm. By making it 0.5 mm or more, even if there are some irregularities inside the pipe, it is possible to stably cover it with paint and prevent unpainted areas, while by making it 3 mm or less, it is possible to stably solidify the paint.

[0032] In the present method, the mixing of the resin material and the antibacterial agent containing silver is not limited as long as the effect of the present method can be obtained, but it is preferable to mix the antibacterial agent containing silver with the base agent or hardener in advance, and then mix the base agent or hardener containing silver with the hardener or base agent that is paired with it. In this way, it is possible to sufficiently disperse the silver particles before hardening begins by mixing the base agent and hardener, which has the effect of allowing the mixture to be mixed more uniformly.

[0033] As described above, this method provides antibacterial protection for the inside of piping, which can maintain a clean state.

[0034] As is clear from the above description, the pipe protected by the above method becomes a covered and protected pipe. EXAMPLES

[0035] The effects of the invention according to the above-mentioned embodiment were actually carried out, and a biofilm evaluation test was carried out to confirm the effects. The details are described below.

[0036] (Test piece) A total of six types of materials were used in this biofilm evaluation test (see Table 1 below). [Table 1]

[0037] The test specimens were prepared by cutting them from pipes (inner diameter approx. 50 mm) that were incorporated into the experimental system described later. As will be clear from the description below, some of the test specimens had an antibacterial coating on the inside walls. This was achieved by mixing 4.0% by weight of commercially available silver-loaded zeolite (antibacterial agent Zeomix manufactured by Sinanen Zeomix) into resin and spraying it to paint the inside surface of the pipes.

[0038] For test pieces A to D, transparent polyvinyl chloride pipes (hereafter referred to as PVC raw pipes in this experiment; JIS K6741) were used as the piping material. On the other hand, test pieces E and F were carbon steel raw pipes (JIS G3452) that had been hot-dip galvanized for sewage use (commonly known as white gas pipes), with a plating thickness of 34 μm (equivalent to JIS G3302 Z18).

[0039] Test piece A is coated with approximately 0.1 mm of a PVC-specific primer liquid (urethane resin system) containing commercially available silver-loaded zeolite powder, and test piece B is a material in which the inside of the raw PVC pipe is coated with 0.5 mm of epoxy resin that does not contain an antibacterial agent. Test piece C is the raw PVC pipe itself with no antibacterial coating applied. Test piece D is a material in which the inside of the raw PVC pipe is coated with 0.5 mm of epoxy resin containing commercially available silver-loaded zeolite powder. The test pieces are galvanized steel sheets with no antibacterial coating applied, whereas test piece F is coated with 0.5 mm of epoxy resin containing commercially available silver-loaded zeolite powder.

[0040] The reason for focusing on these six types of test pieces in particular is that they were thought to be the optimal combination for quantitatively understanding the behavior of biofilm formation on carbon steel pipes and polyvinyl chloride pipes, which are commonly used in kitchen drainage pipes in apartment buildings, and for clarifying the effects of antibacterial coatings in this study.

[0041] (Biofilm formation test) For the biofilm formation test, a piping system was constructed using the six different materials shown in Table 1, and a solution was prepared from the sink to simulate a normal home environment. The solution consisted of miso soup, rice water, cooking oil, soy sauce, sauce, sugar, butter, dishwashing water (with detergent), juice, and tap water for cleaning, with a total volume of 20 L, and was designed to simulate one standard kitchen drainage run. A specified amount of the solution was run through the piping several times a week, allowing the inner walls of the piping to be exposed. Details of the solution composition are shown in Table 2. [Table 2]

[0042] This simulated wastewater solution was run through the piping system shown in Figure 4. 20 L of wastewater solution was run through a translucent container placed in the upper left, for a total of 40 L per day, exposing the inside of the piping system to the solution. Every month, the pipes were cut into pieces several tens of millimeters thick, and the condition of the inner walls was recorded by photographing and used for biofilm evaluation tests.

[0043] (Biofilm evaluation test) After the exposure, the pipe was cut into slices of a given size, and then the amount of biofilm formation was evaluated. The biofilm formation was first evaluated by visual inspection.

[0044] Biofilms can certainly be observed with the naked eye, but they are largely recognized by sensation, such as changes in color, texture, slimy appearance, etc. It is generally believed that the process is biofilm formation → growth → corrosion, or biofilm formation → growth → scale formation, but strictly speaking, it is difficult to distinguish between biofilms, corrosion products, and scale.

[0045] However, as mentioned above, if scale formation and corrosion are caused by biofilms, then corrosion (for metal materials) and scale formation (for metal and polymer materials) that are clearly visible to the naked eye are one of the standards for evaluating the degree of biofilm formation as a precursor. Biofilm evaluation was performed by staining with 0.1% crystal violet.

[0046] The cut pipes were placed in appropriate plastic containers, and 0.1% crystal violet solution was poured in until the entire inner surface of the pipes was soaked. The pipes were left to stand for 30 minutes, after which the crystal violet solution was removed and the pipes were washed with water three times. The inner surface of the pipes stained with crystal violet was then wiped with a nonwoven cloth (5 cm x 5 cm) soaked in ethanol, and placed in a 10% sodium dodecyl sulfate solution to dissolve it. After thoroughly stirring this solution, 200 μL was drawn out using a pipette.

[0047] First, this extract was filled into a 96-well plastic well and the absorbance was measured by irradiating it with 570 nm light using a plate reader (Multiscan, Thermofisher). However, it was observed that the measurement limit was often exceeded for some samples, so the absorbance was measured for the extract obtained by diluting the extract 10-fold, and the absorbance values ​​per unit area of ​​the inner surface were compared between each sample.

[0048] In addition, R values ​​were calculated using carbon steel and PVC raw pipes as controls, and a comparative study was conducted. The biofilm index is an index proposed by the Council of Technology for Antibacterial Products, and is currently being considered as part of international standardization activities. In this study, it is called the biofilm index. In this study, R is defined as follows:

[0049] Formula (1) R = [(absorbance of target sample - absorbance of reference sample) / absorbance of reference sample)] x 100 (%)

[0050] (Experimental Results) (Corrosive organisms, scale formation) Representative examples of corrosion products or scale formation on various test pieces are shown in Figures 5 and 6. Figure 5 is a photograph of the inside of each sample pipe one month after the start of the exposure test. Meanwhile, Figure 6 shows the condition inside the pipe after seven months.

[0051] It was observed that scale gradually formed on all test pieces. It was observed that "dirt" formed on all test pieces and progressed to scale.

[0052] In the case of test piece (A) (Figures 5 and 6 (1)), the appearance of the inside of the pipe after seven months seemed to show that scale formation had progressed considerably. Similarly, test piece (B) (Figures 5 and 6 (2)) also showed noticeable scale formation after seven months, to the point that traces of the passage of seven months were visible. This test piece (A) was coated with urethane resin containing an antibacterial agent, while test piece (B) was only coated with epoxy resin. Based on the state of scale formation in the results of these two test pieces, the effect of the antibacterial agent was not noticeable. At this point, it was hypothesized that this may be because the thickness of the urethane resin coating was 0.1 mm, which was thinner than that of test piece (B).

[0053] On the other hand, since the epoxy resin coating agent alone exhibits a certain degree of antibacterial properties, we proceeded with the experiment with the assumption that there may be little difference between the two.

[0054] Figures 5 and 6 (3) show the results when no coating was applied to the PVC raw pipe (test piece C). As expected, after one month of exposure (Figures 5 and 6 (3)), it was difficult for antibacterial properties to be expressed, and scale formation was observed, which became more noticeable after seven months.

[0055] Figure 5 and Figure 6 (4) show a sample with an antibacterial coating applied to the inner wall of a PVC raw pipe (test piece D). From the results after exposure, it can be seen with the naked eye that when coated with an antibacterial agent, the formation of scale is significantly suppressed compared to the results of test piece B, which does not have an antibacterial agent added.

[0056] The above results are for PVC pipe, but the results for metal pipe (specimen made of hot-dip galvanized carbon steel) often used for kitchen drainage pipes are shown in (5) and (6) in Figures 5 and 6, respectively. (5) in Figures 5 and 6 is the specimen without antibacterial coating (specimen E), and after 1 month and 7 months, no significant progress in scale formation was observed.

[0057] At this point, judging only from the visual results, it seemed that the antibacterial properties of zinc in the galvanized steel sheet inhibited the formation of biofilms. Meanwhile, Figures 5 and 6 (6) show the results for a sample in which an antibacterial coating was applied after hot-dip galvanizing of carbon steel (test piece F). Comparing this with the results for test piece E (Figures 5 and 6 (5)), it was found that the effect of inhibiting scale formation was actually suppressed by applying a coating containing an antibacterial agent. As brown iron oxide was clearly visible, unlike the case of the antibacterial coating on the raw PVC pipe, it appears that the phenomenon in which zinc becomes ions and exerts an antibacterial effect upon application was inhibited, which induced the dissolution of the iron base and promoted the formation of scale.

[0058] (Changes in biofilm formation over time) The above results of the macroscopic observations are shown with time in Figures 5 and 6. However, although these results alone allow for a qualitative estimation and indirect inference of biofilm formation, it is difficult to specifically and directly quantify it, and one has to say that they are somewhat lacking in objectivity. Therefore, these test pieces were cut into slices, and the inner surfaces were stained with crystal violet, which is often used to quantify biofilms, in an attempt to quantify the amount of biofilm formation.

[0059] Figures 7 and 8 show the results of exposure for a set period of time (Figure 7 shows the result of exposure for one month, and Figure 8 shows the result of exposure for seven months) corresponding to the morphological observation by the naked eye. The inside of the pipe was dyed with crystal violet, and the absorbance of the solution extracted with sodium dodecyl sulfate was measured. The horizontal axis shows each sample, and the vertical axis shows the corresponding absorbance. The higher the absorbance value on the vertical axis, the higher the amount of biofilm formed. What was characteristic after one month was that the amount of biofilm formed was higher on the PVC raw pipe than on the white gas pipe. This is consistent with the results estimated from the scale formation state observed with the naked eye, and is thought to be the effect of zinc ions. The amount of biofilm formed was higher on test piece F, which had an antibacterial coating on the zinc plating layer, compared to the case with only the zinc plating layer (test piece E), which is also consistent with the results observed with the naked eye.

[0060] In contrast, in the PVC raw pipe test pieces, the amount of biofilm formed was slightly lower in test pieces A and D, which had an antibacterial coating, compared to the PVC raw pipe (test piece C) alone. It is thought that a certain degree of antibacterial effect from the coating was already reflected after one month. Test piece B, which did not have an antibacterial coating, also had a lower amount of biofilm formed than the PVC raw pipe, but this can be attributed to the fact that biofilm formation was less likely to occur on the epoxy resin compared to the PVC raw pipe. It is not clear from the results of this experiment alone whether this is because the epoxy resin has a certain degree of antibacterial properties, or whether there is another reason why bacteria are less likely to adhere to the epoxy resin compared to the PVC raw pipe.

[0061] On the other hand, looking at the results in Figure 8, after about six months, it can be seen that test pieces A and D, which were PVC raw pipes with an antibacterial coating, had a low amount of biofilm formation, and that the expression of antibacterial properties suppressed biofilm formation. For test piece B, the amount of biofilm formed was slightly greater than that on the raw PVC pipe, indicating that the biofilm suppression effect was disappearing. In the case of the coating that did not contain an antibacterial agent (test piece B), biofilm formation was not suppressed because antibacterial properties were not expressed, and instead there was more biofilm than on the raw PVC pipe. We believe that we have been able to confirm that the effect of antibacterial properties in suppressing biofilms became more pronounced over time.

[0062] In the case of the carbon steel sample that had been hot-dip galvanized, biofilm formation was initially suppressed by the effect of the zinc plating (Figure 7), but for the test pieces that had been in use for six months, the difference became smaller when compared to the raw PVC pipe, suggesting that the effect of zinc was gradually decreasing. This is thought to be due to the fact that for zinc, a brown base iron oxide was observed to form on the material surface, and this formation gradually inhibited the dissolution of zinc, thereby reducing the antibacterial effect. Comparing the results of test piece F with those of test piece E, no significant biofilm suppression effect was observed, as in the case of the antibacterial coating on the raw PVC pipe (test piece D). In the case of the coating on the raw carbon steel pipe, it is thought that the formation of iron ions counteracted the effect of adding silver.

[0063] To quantitatively evaluate biofilm formation, it is recommended to calculate the R value shown in formula (1). This value is calculated from the absorbance value of the effect of the test piece that has been treated with anti-biofilm properties. Since the absolute value of absorbance varies depending on the test piece and also on the experimental conditions and lot differences, this amount was introduced for each test to compare with the untreated product. Using this, the R value was calculated based on the value of the original PVC pipe, and is shown in Figures 9 and 10. The smaller the value on the vertical axis, the more biofilm formation is suppressed.

[0064] Figure 9 shows that the antibacterial effect of zinc plating is evident in the short term, while the biofilm-suppressing effect of the PVC pipe is smaller and the effect of the antibacterial coating is not clear. Figure 10 shows the results after 7 months of exposure, and clearly shows the effect of the antibacterial coating on biofilm suppression. The biofilm index R value is currently an index proposed by the Biofilm Committee of the Society of Antibacterial Products (SIAA), and it is empirically considered that when its absolute value exceeds 60% of the comparison target, it is clearly antibiofilm to the comparison target. In addition, since the variation is said to be approximately ±20%, when comparing the test pieces in this study from this perspective, it is clear that the antibacterial coating of the PVC pipe reliably suppressed biofilm, and this becomes increasingly clear as the exposure continues for a long period of time, and it is also clear that the biofilm suppression becomes higher over a long period of time compared to the zinc-plated carbon steel pipe.

[0065] From the above, it was found that antibacterial coatings are effective in inhibiting biofilms, that this is greater both on raw PVC pipes and on hot-dip galvanized carbon steel, and that the difference becomes clear over long-term exposure. In addition, when comparing antibacterial coatings on white gas pipes and raw PVC pipes, it was found that although the mechanisms of biofilm inhibition are different, the sample with the antibacterial coating on the raw PVC pipe had a greater biofilm inhibition effect over time. As it has been previously known that there is a causal relationship between biofilms and scale formation, it is presumed that the antibacterial coating also contributes greatly to the reduction of scale. As for the mechanism, it is currently thought to be as follows:

[0066] Biofilms are slime that adhere to material surfaces for the purpose of obtaining nutrients, etc., and when their number increases and exceeds a certain value, they undergo a process of signal transmission between bacteria called quorum sensing, and are formed by the production of polysaccharides. This slime then continues to grow and increase as a biofilm, absorbing organic and inorganic substances from the surrounding environment or base material, and eventually continues to grow and increase as scale. In this time change, the key in the initial stage is the increase in the number of attached bacteria. This is closely related to antibacterial properties. By imparting antibacterial properties to the material of the inner wall of the pipe, the adhesion of bacteria is suppressed, making it difficult for the number of bacteria to increase. It is thought that this is why biofilm formation is suppressed. The results of this study are thought to show that antibacterial coating with the addition of silver exhibits antibacterial properties, which results in the suppression of biofilm. It is thought that the suppression of biofilm also suppresses scale formation.

[0067] As described above, the present invention can provide a method for inhibiting scale formation by inhibiting biofilms. [Industrial Applicability]

[0068] INDUSTRIAL APPLICABILITY The present invention has industrial applicability as a method for inhibiting scale formation by inhibiting biofilms.

Claims

1. A method for inhibiting biofilm formation in a drainage pipe, comprising the step of applying paint containing an antibacterial agent to a drainage pipe in a facility made of resin or metal.

2. The method for inhibiting biofilm formation according to claim 1 , wherein the drain pipe is a polyvinyl chloride pipe.

3. The method for inhibiting biofilm formation according to claim 1 , wherein the drain pipe is made of carbon steel.

4. The method for inhibiting biofilm formation according to claim 1, wherein the drain pipe is a metal pipe having a zinc-plated inner surface.

5. The method for inhibiting biofilm formation according to claim 1, wherein the antibacterial agent is silver-loaded zeolite.

6. The method for inhibiting biofilm formation according to claim 1 , wherein the weight of the antibacterial agent is in the range of 2 to 10 parts by weight, based on 100 parts by weight of the entire paint.

7. A method for inhibiting scale formation in drainage pipes in a facility, comprising the step of applying a paint containing an antibacterial agent to the drainage pipes.

8. A method for inhibiting the formation of scale and biofilm in drainage pipes in a facility, comprising the step of applying a paint containing an antibacterial agent to the drainage pipes.

Citation Information

Patent Citations

  • Pipeline regeneration method for condominium and the like

    JP2002239488A